Engineering the Surface of Ti3C2 MXene Nanosheets for High Stability and Multimodal Anticancer Therapy - Chiranjeevi Korupalli; Kai-Long You; Girum Getachew; Akash S. Rasal; Worku Batu Dirersa; Mochamad Zakki Fahmi; Jia-Yaw Chang (Pharmaceutics, 2022)
The surface of Ti3C2 MXene nanosheets (TC NSs) was first modified with the antioxidants sodium ascorbate (SA) and dopamine (DA) (DSTC NS) to improve their stability in oxidative and hydration environments and thereby improve their bioapplications. This novel approach not only improved MXene stability by arresting oxidation but also increased the available functional groups for further functionalization with various biomolecules. The DSTC NSs were then sequentially conjugated with enzyme glucose oxidase (GOx) and photosensitizer Ce6 to render the obtained CGDSTC NSs with glucose starvation and photodynamic therapeutic properties and thus attain high efficiency in killing cancer cells through the cooperative effect. The as-synthesized CGDSTC NSs demonstrated tremendous photothermal effect with conversion efficiency of 45.1% and photodynamic (ROS generation) properties upon irradiation with 808 and 671 nm lasers. Furthermore, it was observed that the enzymatic activity of CGDSTC NSs increased upon laser irradiation due to enhanced solution temperature. During in vitro studies, the CGDSTC NSs exhibited cytocompatability to HePG2 and HeLa cells under nonstimulus conditions. However, they elicited more than 90% cell-killing efficiency in the presence of glucose and laser irradiation via the cooperative effect between starvation therapy and phototherapy. These results indicate that CGDSTC NSs could be used as potential therapeutic agents to eradicate cancers with no or few adverse effects. This surface modification approach is also simple and facile to adopt in MXene-based research.